Gender and Transitional Justice - Muddell, Kelli; Hawkins, Sibley (International Center for Transitional Justice (ICTJ), 2018)
Reparative justice measures seek to repair, in some way, the harm done to victims as a result of human rights violations committed against them. This means that by their very nature, such measures must be responsive to both the context in question and the lived reality of victims. Gender sensitivity is also an integral part of reparative justice because the consequences of human rights violations in victims’ lives are often inextricably linked with victims’ gender. Even when women and men suffer the same human rights abuses, the harms associated with these violations, and victims’ corresponding needs and priorities, may be different. In contexts of widespread violations of human rights, women often find themselves in situations of greater vulnerability than men because of the economic and social inequalities they face even during peacetime. Moreover, shame and stigma associated with certain crimes, such as sexual violence, can create obstacles for victims to receive accountability, truth, and redress. This is true for all victims of sexual and gender-based violence, not only women. In fact, male victims may have an even harder time accessing reparations for sexual violence crimes because it is often assumed that women are the only victims. Because of these dynamics, reparative justice measures must be designed to address the genderspecific harms faced by victims, align with their needs and priorities, and make sense for victims given their day-to-day realities. Reparations should reflect the nature of the violations and the genderspecific consequences that result. Unsurprisingly, past reparations programs have not always done this.
A TRAINING MODULE SERIES
Keywords: Reparations; Gender Justice; Victim-Centered Approach; Legal Accountability; Post-Conflict Recovery